Proliferating cell nuclear antigen and nucleolar organizer region for differential diagnosis of dysplasia and adenocarcinoma in gastric biopsies. - Ozercan, I.H.; Bahçecioglu, I.H.; Ozercan, M.R.; Bozlak, N.; Dogan, C.; Yekeler, H. (My University, 2000)
INTRODUCTION: The value of proliferating cell nuclear antigen (PCNA) and nucleolar organizer region (AgNOR) for differential diagnosis of normal mucosa, dysplasia and adenocarcinoma in gastric endoscopic biopsies, and correlation between these two methods were evaluated. METHODS: 15 gastric endoscopic biopsy samples from normal mucosa, 15 from areas of dysplasia and 15 from low grade adenocarcinoma were studied. AgNOR and PCNA immunostaining were applied to paraffin sections. RESULTS: Mean AgNOR value and PCNA-labeling index were the lowest in normal mucosa and the highest in adenocarcinoma. Mean (SD) AgNOR numbers were 2.9 (0.3) in normal mucosa, 5.9 (1.7) in dysplasia and 15.7 (2.8) in adenocarcinoma. PCNA-labeling index was 2.4 (1.1) in normal mucosa, 27.5 (4.6) in dysplasia and 42.1 (5.3) in adenocarcinoma. The differences between normal mucosa and dysplasia, and between dysplasia and adenocarcinoma were significant (p < 0.001). Overlapping values were observed in AgNOR counts between normal mucosa and dysplasia, and in PCNA-labeling indices between dysplasia and adenocarcinoma. No correlation was found between AgNOR and PCNA. CONCLUSION: Though mean AgNOR values and PCNA indices were significantly different between normal mucosa, dysplasia and adenocarcinoma, these could not be used in differential diagnosis because of overlapping values between groups.
Keywords: Adenocarcinoma; Biopsy; Diagnosis, Differential; Gastric Mucosa; Humans; Immunoenzyme Techniques; Nucleolus Organizer Region; Proliferating Cell Nuclear Antigen; Silver Staining; Stomach Neoplasms; cycline; adenocarcinoma; article; biopsy; chromosome NOR; differential diagnosis; enzyme immunoassay; human; methodology; pathology; silver staining; stomach mucosa; stomach tumor